(untitled) (Chittagong University Journal of Biological Sciences, 2024)
A pot experiment was conducted to study the effects of biogas digestate from cowdung and poultry manure,and raw cow dung and poultry manure on the growth and yield of spinach (Spinacea oleracea L.)at glass house of the Department of Soil Science,University of Chittagong, Bangladesh. Treatments with three replications were as follows:T1(control),T2(100%N of recommended dose@90 kg N ha-1 from urea),T3(100% N from cow dung digestate),T4(100% N from poultry manure digestate),T5(100% N from raw cow dung),T6 (100% N from raw poultry manure),T7(50% N from urea+ 50%N from cow dung digestate), T8(50% N from urea+ 50% N from poultry manure digestate)T9(50% N from urea+ 50% N from raw cow dung) and T10(50% N from urea+ 50% N from raw poultry manure).Pots were arranged in a randomized block design. Results showed that there were significant variations among the treatments in number of leaves in each plant,plant height, and fresh and dry weight of shoot and root. Treatments T7 and T8 had significantly increased number of leaves and plant height at 15,25 and 40 DAS. Treatment T7 showed the best performance compared to other treatments in producing fresh and dry weight of shoot and root biomass of spinach. The Chittagong Univ. J. B. Sci. 9(1&2):19-28,2019